CORRELATION BETWEEN POLITICAL MISTRUST AND PRE-RETIREMENT ANXIETY AMONG CIVIL SERVANTS IN ENUGU STATE, NIGERIA - Ikwuegbu, Pauline N. (International Journal of Advance Research in Education & Literature (ISSN 2208-2441), 2022)
The present study investigated the correlation between political mistrust and pre-retirement. Two hundred and thirty-six Enugu state civil service employees participated in the study. The respondents comprising males and females, were conveniently selected from various agencies, departments, and ministries in the state civil service. They completed a self-report measure of the political mistrust and the Pre-retirement Anxiety Scale. The Pearson's product-moment correlation model conducted on the data showed a statistically significant, moderate positive correlation between political mistrust and pre-retirement anxiety, r (234) = .47, p < .001, with political mistrust contributing about 13.7% of the variation in pre-retirement anxiety among the civil servants. The finding has implications for employees' well-being and job productivity